Asymmetrical domain wall propagation in bifurcated PMA wire structure due to the Dzyaloshinskii-Moriya interaction - Lew, Wen Siang (2017)
Controlling domain wall (DW) motion in complex magnetic network structures is of paramount significance for the development of spin-based devices. Here, we report on the dynamics of a propagating DW in a bifurcated ferromagnetic wire with perpendicular magnetic anisotropy (PMA). The Dzyaloshinskii-Moriya interaction (DMI) in the wire structure induces a tilt angle to the injected DW, which leads to a quasi-selective propagation through the network branch. The DW tilting causes a field interval between DWs to arrive at Hall bars in the individual branches. Micromagnetic results further show that by tailoring the strength of the DMI, the control of DW dynamics in the PMA complex network structures can be achieved.